Solução de problemas em semiespaço na dinâmica de gases rarefeitos baseada em modelos cinéticos - Cromianski, Solange Regina (2012)
The method discrete ordinates is used to solve problems involving rarefied gas dynamics. In this work, a version of the analytical method discrete ordinates (ADO) is used to solve problems in a semi-infinite. The complete analytical development, in cartesian coordinates, the solution of the Thermal-Slip and Viscous-Slip problems is presented, for four kinetic models: BGK model, S model, Gross Jackson model and MRS model in a unified approach. In addition, to describe the interaction between gas and surface, we use the Cercignani-Lampis boundary condition defined in terms of the coefficients of accommodation of tangential momentum and energy accommodation coefficient kinetic corresponding the velocity normal. Numerical results are presented, where we obtain quantities of interest, such as: velocity profile and heat flow profile, which were implemented computationally through the FORTRAN program.